Determinants of Malaysia national savings account / Raja Nabila Syazwanee Raja Hazman Shah - Raja Hazman Shah, Raja Nabila Syazwanee (2015)
This study is to investigate the determinants of Malaysia national saving account by using data from the World Bank Data and EIU Country Data. The financial data have been tested in this study in determining factor that influences the Malaysia national saving account. The variables considered are growth domestic products, interest rate, consumers' price index and inflation rate. The sample of this study comprises of 30 observations of the independent and dependent variables on a yearly basis over 30 years period from 1985 to 2014. The data can be found from World Data Bank and EIU Country Data. Interactive software package, E-views will be used for regression analyzing the data that have been collected. The variables basically from the previous research paper that related to the determinants of Malaysia national Saving Account. The results of this research would determine which financial data variables have significant affect towards in national saving account of Malaysia.